2015
DOI: 10.1039/c5ib00092k
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the finger instability in an expanding cell monolayer

Abstract: Collective motion occurs in many biological processes, such as wound healing, tumor invasion and embryogenesis. Experiments of cell monolayer migration have revealed the spontaneous formation of finger-like instabilities, with leader cells at their tips. We present a particle-based model for collective cell migration, based on several elements that have been found experimentally to influence cellular movement. Inside the bulk we include velocity alignment interactions between neighboring cells. At the border c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
90
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(97 citation statements)
references
References 40 publications
7
90
0
Order By: Relevance
“…In parts of the phase diagram, we observe a fingering instability [90][91][92][93] where regions a few cells wide migrate outward from the centre, as shown in Fig 6e. When τ α drops below approximately 10, we observe that the fluctuations of the boundary already present in Fig 6d become unconstrained. This is a mechanically unstable regime: Eventually, these cells will detach, a process we are not yet able to model due to the topological change that it would imply (see, Fig 3).…”
Section: Activity Driven Fluidisation Phase Diagrammentioning
confidence: 90%
“…In parts of the phase diagram, we observe a fingering instability [90][91][92][93] where regions a few cells wide migrate outward from the centre, as shown in Fig 6e. When τ α drops below approximately 10, we observe that the fluctuations of the boundary already present in Fig 6d become unconstrained. This is a mechanically unstable regime: Eventually, these cells will detach, a process we are not yet able to model due to the topological change that it would imply (see, Fig 3).…”
Section: Activity Driven Fluidisation Phase Diagrammentioning
confidence: 90%
“…CIL implies that cells at the edge of a tissue exert the strongest substrate traction forces. The fact that cells at the edge might behave differently from cells in the tissue interior was observed not only in cell clusters that form supercells (7)(8)(9)(10)(11) and spreading tissues experiencing kenotaxis (16) but also, with leader cells at the tip of fingers guiding the closure of model wounds (29,47). Recently, it was shown that cell clusters consisting of nonchemotactic single cells can exhibit collective chemotaxis through CIL (33,35,48).…”
Section: Discussionmentioning
confidence: 99%
“…However, those macroscopic models cannot provide a conclusive description of how cells generate forces, align, divide, and maintain tissue integrity on an individual cell level. Cellular Potts or vertex models (20)(21)(22), phase field models (23)(24)(25), and particle models (26)(27)(28)(29) use a bottom-up approach instead and focus on individual cell properties. However, these models were mainly used to explore cellular flow patterns and tissue morphologies, and they…”
mentioning
confidence: 99%
“…We have recently developed a theoretical model that describes the expansion of cellular monolayer [8], which includes a mechanism for dynamic instability of the edge propagation. This instability is driven by a positive feedback between the local convex curvature of the edge [9], and the tendency of cells along the edge to have motile forces directed outwards ( figure 1(a)).…”
Section: Introductionmentioning
confidence: 99%